Intervención optométrica en paciente masculino de 25 años edad con astigmatismo miopico. - Santillán García, Iván Alexander (2024)
The patient is a 25-year-old man with a complex vision problem in the cornea or lens, causing problems both near and far. This is known as astigmatic myopia, which is a combination of myopia (difficulty seeing distant objects) and astigmatism (uneven curvature). The patient experiences symptoms that make daily life difficult, such as blurred vision, headaches and double vision. After a thorough evaluation, the diagnosis is determined to be simple myopic astigmatism. Various examinations were performed, such as visual acuity tests, control of pupillary reflexes, evaluation of ocular mobility and refraction, to reach an accurate diagnosis. In order to improve the patient's vision and comfort, a monofocal corrective lens with a blue light filter was selected, since the patient spends much of his time in front of screens. The use of corrective lenses generated a notable improvement in the patient's visual acuity, which in turn significantly reduced the symptoms he experienced. This shows that the treatment not only improved his vision, but also relieved his discomfort. The patient was recommended to continue performing periodic visual checks in order to monitor his progress and take additional measures if necessary.